Sudden cardiac arrest as first manifestation of malignant mitral valve prolapse in a young patient: a case report and review of the literature - Bigdelu, Leila; Bitar, Zouheir; Maadarani, Ossama (European Journal of Case Reports in Internal Medicine, 2024)
Mitral valve prolapse (MVP) is a primary valvular disease of the mitral valve with a prevalence of 2.4% of the general population. Valve abnormalities range from simple fibroelastic deficiency of the leaflets to diffuse myxomatous degenerative changes. MVP is a usually a benign condition. However, the scattered reports of sudden cardiac death in patients with MVP in the absence of severe mitral insufficiency or coronary artery disease suggest the existence of a malignant phenotype of MVP. We report a case of a young female who survived life-threatening arrhythmias and cardiac arrest and was found to have characteristic features of the malignant phenotype of MVP and had an implantable cardioverter defibrillator as a secondary prevention.